An estimation of exergy consumption paterns of energy‐intensive building service systems - Biekša, Darius; Martinaitis, Vytautas; Šakmanas, Aloyzas Algimantas (Journal of Civil Engineering and Management, 2006)
This paper represents the estimation of life cycle exergy consumption for building service systems (BSS). The investigation explores public building engineering systems, which are the most energy‐intensive. These include heating, ventilating and lightning. The exergy consumption analysis is divided into three parts: systems production, operating and maintenance (O&M) and decommissioning. The differences between them consist in different exergy demand and consumption intensiveness. The main attention is paid to BSS O&M investigation by categorising and defining exergy demands within the building. Exergy consumption for BSS O&M period is estimated as certain amount of exergy that should be supplied to the buildings boundaries. In this investigation of building engineering systems, 4 typical buildings are explored for the Vilnius’ city conditions in Lithuania. Pastato inžinerinių sistemų pirminės energijos poreikių įvertinimas Santrauka. Šiame darbe analizuojamas pastato inžinerinėms sistemoms reikalingi pirminės energijos poreikiai. Tyrime nagrinėjamos dideliu energijos imlumu išsiskiriančios visuomeninių pastatų inžinerinės sistemos. Tai šildymas, vėdinimas ir apšvietimas. Pirminės energijos poreikių analizė suskirstyta į sistemų įrengimą, naudojimą bei išardymą, t. y. etapus, besiskiriančius pagal pirminės energijos poreikio mastą ir vartojimo intensyvumą. Pagrindinis dėmesys darbe skiriamas sistemų naudojimo laikotarpiu suvartojamos pirminės energijos sąnaudoms identifikuoti. Pastato inžinerinių sistemų pirminės energijos poreikiai yra įvertinti kaip iki pastato ribos būtinas patiekti pirminės energijos kiekis. Tirti 4 pastatai, kuriems buvo pritaikytos Vilniaus miesto klimato sąlygos. Reikšminiai žodžiai: pastatų inžinerinės sistemos, pirminės energijos sąnaudos, procesų integracija. First Published Online: 14 Oct 2010